Anatomical Intelligence: Live coding as performative dissection. - Chicau, Joana; Reus, Jonathan (Organised Sound, 2023)
This article describes the method of 'dissective' live coding, as developed through the artistic-research project Anatomies of Intelligence. In this work we investigate how live coding can be used as an approach for performative explorations of a data corpus and a machine learning algorithm operating on this corpus. The artistic framework of this project collides early Enlightenment-era anatomical epistemologies with contemporary machine learning, creating a fertile space for novel, embodied artistic methods to emerge. We engage audiences in an immersive, live-coded experience where image and sound are driven by our dissective approach, revealing the underlying rhythms and structures of a machine learning algorithm running live on an artist-made dataset. To support these performances we have developed a custom browser-based software, the Networked Theatre, used for both hybrid in-person/online audiovisual performances. In this article we describe this work and reflect on our experience as performers and audience feedback, which suggests that our dissective method of live coding, based on examining 'ready-made' algorithms, offers a unique experiential entryway into the bodies of machine learning and data corpi.